Principles of data management : facilitating information sharing - Gordon, Keith (BCS, The Chartered Institute for IT, 2022)
Data is a valuable corporate asset and its effective management is vital to an organisation's success. This professional guide covers all the key areas of data management, including database development and corporate data modelling. It is business-focused, providing the knowledge and techniques required to successfully implement the data management function. This new edition adds chapters on linked data, concept systems and big data and artificial intelligence.
"BCS Learning & Development Limited"
Part 1: PreliminariesChapter 1 Data and the enterpriseChapter 2 Databases and their developmentChapter 3 What is data management?Part 2: Data AdministrationChapter 4 Corporate data modellingChapter 5 Data definition and namingChapter 6 MetadataChapter 7 Data qualityChapter 8 Data accessibilityChapter 9 Master data managementPart 3: Database and Repository AdministrationChapter 10 Database administrationChapter 11 Repository administrationPart 4: The Data Management EnvironmentChapter 12 The use of packaged application softwareChapter 13 Distributed data and databasesChapter 14 Business intelligenceChapter 15 Object orientationChapter 16 MultimediaChapter 17 Integrating data and web technologyChapter 18 Linked dataChapter 19 Concept systemsChapter 20 Big data and artificial intelligenceAppendicesAppendix A Comparison of data modelling notationsAppendix B Generic data modelsAppendix C HTML and XMLAppendix D Techniques and skills for data managementAppendix E Data strategyAppendix F International standards for data managementAppendix G The BCS Data Management Essentials syllabus.
Keywords: Database management.; Business -- Data processing.; Management -- Data processing.; elektronické knihy; electronic books